2020
DOI: 10.1121/10.0000621
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cues for tone-in-noise detection using decision variable correlation in the budgerigar (Melopsittacus undulatus)

Abstract: Previous studies evaluated cues for masked tone detection using reproducible noise waveforms. Human results founded on this approach suggest that tone detection is based on combined energy and envelope (ENV) cues, but detection cues in nonhuman species are less clear. Decision variable correlation (DVC) was used to evaluate tone-in-noise detection cues in the budgerigar, an avian species with human-like behavioral sensitivity to many complex sounds. DVC quantifies a model's ability to predict trial-by-trial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
4
10
0
Order By: Relevance
“…7, right). The magnitude of the DVC was generally slightly greater for tone-plus-noise trials than noise trials, as observed previously (Henry et al, 2020), and somewhat lower for lowlevel, higher-frequency stimuli (Fig. 8, top left).…”
Section: Ka-exposed and Control Groups Use The Same Energy-based And Envelope-based Cues For Tin Detectionsupporting
confidence: 85%
See 4 more Smart Citations
“…7, right). The magnitude of the DVC was generally slightly greater for tone-plus-noise trials than noise trials, as observed previously (Henry et al, 2020), and somewhat lower for lowlevel, higher-frequency stimuli (Fig. 8, top left).…”
Section: Ka-exposed and Control Groups Use The Same Energy-based And Envelope-based Cues For Tin Detectionsupporting
confidence: 85%
“…In contrast, spontaneous activity is unimodally distributed in birds rather than bimodal as in mammals, and units without spontaneous activity are not observed. In light of these basic physiological similarities, as well as findings of human-like behavioral performance in normal-hearing budgerigars (Saunders et al, 1979;Henry et al, 2017bHenry et al, , 2020Dent et al, 2000;Dooling et al, 2000), it seems promising that behavioral results in AN-damaged budgerigars might be observed in humans or mammalian animal models for the same degree of neural loss.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations